Do Time of Birth, Unit Volume and Staff Seniority Affect Neonatal Outcome in Deliveries at ≥34+0 Weeks of Gestation?. Issue 1 (March 2019) - Reif, P.; Pichler, G.; Griesbacher, A.; Lehner, G.; Schöll, W.; Lang, U.; Hofmann, H.; Ulrich, D.
Abstract : ( BJOG . 2018;125:884–891) While women can go into labor at any time, most maternity units are better staffed during daytime working hours. A higher incidence of adverse events has been associated with out-of-hours periods in some studies, but this relationship was not confirmed in others. This study aimed to evaluate whether unit volume, time of birth, and staff seniority during delivery were associated with adverse neonatal outcomes in a province in Austria. The study hypothesized that out-of-hours-deliveries and deliveries at units with fewer deliveries would be associated with an increased risk of adverse outcomes, and also hypothesized that deliveries attended by junior staff and midwives would have better outcomes when compared with deliveries attended by senior staff, as senior staff are likely to be involved in complicated pregnancies and deliveries.